Metafísica y bioética I: «metabioética» - Villagrasa, L.C., Jesús (Alpha Omega, 2019)
Summary: The foundations of bioethics are epistemological or real. Metabioethics is bioethics epistemology founded on metaphysics. Bioethics needs metaphysics when, confronted by the reality of bioethical pluralism, looks for a final rational justification of the choices it must make in order to construct one bioethical model. Metaphysics also acts as a mediator between rational and theological knowledge. Key Words: bioethics epistemology, metaethics, philosophy/theology, reason/faith, Sgreccia. Palabras clave: epistemología bioética, metaética, filosofía/teología, razón/fe, Sgreccia.